Multiculturalism in Chinese history in Hong Kong: constructing Chinese identity. Issue 2 (3rd April 2019) - Lin, Cong; Jackson, Liz
ABSTRACT: Teaching young people to understand and appreciate diversity is crucial in Hong Kong efforts for a just and inclusive multicultural society. History is the main place where the cultural identity and values of Hong Kong society have been reflected on, questioned, and problematized in the curriculum, as changes to this curriculum interface with larger social and political changes of the society. Although diversity is emphasized in Hong Kong history curricula, representations of ethnic minorities provided in education may not always be effective toward multicultural aims. This research explores how multicultural content is expressed in Hong Kong Chinese history textbooks. In particular, we focus on how relationships between Han and minority cultures are represented in the texts, using qualitative content analysis. Based on the analysis, we elaborate three main descriptive codes and themes: (1) only majority perspectives are provided, (2) cultural superiority of the dominant group (the Han), and (3) plural monoculturalism, where minority views are treated as threatened and/or as threatening in relation to the society as a whole. We argue that these codes are in contrast with a multicultural stance that aims to enhance social justice and equity in relation to diversity, through providing balanced perspectives, including positive ethnic minority recognition and support for just forms of pluralistic integration.